MONITORING THE RESULTS OF CERVICAL CANCER TREATMENT BASED ON DATA FROM THE SAMARKAND REGIONAL BRANCH OF THE REPUBLICAN SPECIALIZED SCIENTIFIC AND PRACTICAL MEDICAL CENTER OF ONCOLOGY AND RADIOLOGY (Western European Journal of Medicine and Medical Science, 2026)
Cervical cancer is one of the most common malignancies among women. It is the fourth most frequently diagnosed cancer and the fourth leading cause of cancer death in women. This pathology remains a global public health problem, particularly in developing countries. According to GLOBOCAN 2022, 604,000 new cases and 342,000 deaths from cervical cancer were registered worldwide in 2020. Study Objective: To investigate the factors leading to unsatisfactory outcomes (early recurrence, prolonged growth, one-year mortality and survival) after combined and comprehensive treatment of patients with cervical cancer. Study Materials and Methods: A retrospective analysis of outpatient records and medical histories of 1,221 patients with cervical cancer treated between 2014 and 2023 was conducted, based on data from the Samarkand Regional Branch of the Republican Specialized Scientific and Practical Medical Center of Oncology and Radiology. Data from anamnesis, clinical, laboratory, morphological, and instrumental examinations obtained from patients with cervical cancer, outpatient records, medical histories, and cancer registry records.